Analisis Tata Letak Gudang Distribusi Pada Perusahaan Aerospace Menggunakan System Layout Planning Dan Metode Class Based Storage - Poncotoyo, Wahyu; Kania, Dinar; Sihombing, Sarinah; Puspitsa, Sesaria Mardhiani Rachma; Sholihah, Sita Aniisah; Fauziah, Luluk (Institut Transportasi dan Logistik Trisakti, 2024)
Aerospace company faces inefficiencies in warehouse layout and frequent occurrences of both shortages and surpluses of aircraft components. This study employs causal forecasting methods to predict component demand over the next five years and implements the Class Based Storage method. The results show annual demand fluctuations ranging from 651 to 829 items, with high forecasting accuracy. The optimization of the warehouse layout using Class Based Storage successfully enhances storage efficiency and space utilization, contributing to the development of effective warehouse management strategies.